Jeszcze o twierdzeniu Lovella - Zawadzki, Jan (About Lovell's theorem, 2006)
In the article, using the Lovell’s theorem, there have been derived relations between parameters of trends and harmonic components of explained variable and explanatory variables in casualdescriptive models with seasonally changing parameters. The derivation was made on the assumption that there is a function / '(r) in the set of explanatory variables. This function contains a linear trend and varying seasonal term described by means of trigonometric polynomial. The theoretical deliberations were illustrated by an empirical example concerning relations between monthly costs and an amount of output of building materials.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1142, s. 91-98